FAKTOR-FAKTOR YANG MEMPENGARUHI FINANCIAL DISTRESS PADA PERUSAHAAN RITEL DI INDONESIA - Putri Hemas Wijayanti (2021)
This research is using quantitative study aimed to see the influence of leverage, profitability, and firm size on financial distress. The population used in this study are 27 companies in retail sector listed on the Indonesia Stock Exchange (IDX) for the period 2017-2019. The sample techniques using non-probability methode with saturated sampling, using all members of the population as the samples. The type of data used is secondary data. In testing the hypothesis using Regression Logistic Analisys with with E-Views software 10.0 and using Microsoft Excel 2019 in data analysis. The variable of this research are leverage as a measured by Debt to Asset Ratio (DAR), profitability as a measured by Return On Asset (ROA), and firm size as a measured by SIZE. The result of this study indicated that leverage and firm size has no effect on financial distress while profitability has a negative effect on financial distress.